Hematological approaches to multiple myeloma: trends from a Brazilian subset of hematologists. A cross-sectional study - Kerbauy, Lucila Nassif; Parmar, Simrit; Kutner, José Mauro; Gusmão, Breno Moreno de; Hamerschlak, Nelson (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: For the last nine years, hematologists and oncologists have gathered annually at an educational symposium organized by a Brazilian and an American hospital. During the 2015 Board Review, a survey among the attendees evaluated the differences in management and treatment methods for multiple myeloma (MM). DESIGN AND SETTING: Cross-sectional study during an educational hematology symposium in São Paulo, Brazil. METHODS: Hematologists present at the symposium gave responses to an electronic survey by means of mobile phone. RESULTS: Among the 350 attendees, 217 answered the questionnaire. Most of the participants believed that immunotargeting agents (iTA) might be effective for slowing MM progression in heavily pretreated patients (67%) and that continued exposure to therapy might lead to emergence of resistant clones in patients with MM (76%). Most of the physicians use maintenance therapy after hematopoietic stem cell transplantation (95%) and 45% of them would further restrict it to post-transplantation patients with underlying high-risk disease. The first-line drugs used for transplantation-ineligible patients (TI-MM) were bortezomib-thalidomide-dexamethasone (31%), bortezomib-dexamethasone (28%), lenalidomidedexamethasone (Rd; 17%) and melphalan-based therapy (10%). Lenalidomide was the drug of choice for post-transplantation maintenance for half of the participants. No significant differences were observed regarding age or length of experience. CONCLUSION: The treatment choices for TI-MM patients were highly heterogenous and the melphalanbased regimen represented only 10% of the first-line options. Use of maintenance therapy after transplantation was a common choice. Some results from the survey were divergent from the evidence in the literature.